2013
DOI: 10.1371/journal.pone.0054188
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Cytochrome P4502E1 Gene Polymorphisms and the Risks of Alcoholic Liver Disease: A Meta-Analysis

Abstract: BackgroundPrevious studies investigating the association between cytochrome P4502E1 (CYP2E1) polymorphisms and the risk of alcoholic liver diseases (ALD) have yielded conflicting results. Thus, a meta-analysis was performed to clarify the association between CYP2E1 polymorphisms and the risks of ALD.MethodsA comprehensive literature search was conducted to identify the relevant studies. The fixed or random effect model was selected based on the heterogeneity test among studies. Publication bias was estimated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
(52 reference statements)
0
17
0
Order By: Relevance
“…The significance of the pooled effect size was determined by the Z test. Heterogeneity among the studies was assessed using the Q test and the I 2 test as performed in other studies [27], [28]. The DerSimonian and Laird random effects model was used as the pooling method when significant heterogeneity existed; otherwise, the Mantel-Haenszel fixed effect model was used [29].…”
Section: Methodsmentioning
confidence: 99%
“…The significance of the pooled effect size was determined by the Z test. Heterogeneity among the studies was assessed using the Q test and the I 2 test as performed in other studies [27], [28]. The DerSimonian and Laird random effects model was used as the pooling method when significant heterogeneity existed; otherwise, the Mantel-Haenszel fixed effect model was used [29].…”
Section: Methodsmentioning
confidence: 99%
“…Cytochrome P450, family 2, subfamily E, polypeptide 1 (CYP2E1) localizes to the endoplasmic reticulum and is induced by ethanol; thus the enzyme metabolizes both endogenous substrates, such as ethanol, acetone, and acetal as well as exogenous substrates. A recent meta-analysis showed that CYP2E1 might be signifi cantly associated with the development of steatosis, hepatitis, and fi brosis in patients with AFLD [ 63 ]. It is worth mentioning that there are no published GWAS in AFLD, though two efforts are ongoing-one is a multinational GWAS of alcoholic cirrhosis and another is a US-based GWAS of acute alcoholic hepatitis.…”
Section: Ethanol Metabolism and Genetic Variants Infl Uencing Alcoholmentioning
confidence: 99%
“…In particular, rs2031920 (CYP2E1*5) has been well studied as a risk factor for development of alcoholic liver disease with a number of reports of positive associations together with a recent meta-analysis (Zeng et al, 2013). The basis for the association may involve either higher levels of acetaldehyde being produced from ethanol by CYP2E1 in those positive for rs2031920 if, as discussed in Section 2.1.4, the variant is associated with higher levels of transcription.…”
Section: Other Cyp Polymorphism-disease Associationsmentioning
confidence: 99%
“…It is also possible that higher levels of reactive oxygen species occur in those positive for the variant since CYP2E1-mediated reactions generate these species (Koop, 1992). The meta-analysis is a useful summary of all studies on the association of rs2031920 with alcoholic liver disease (Zeng et al, 2013). The overall analysis failed to show an overall significant association for carriage of the variant but the study highlights the small size of most published studies with 21 of the 27 considered involving fewer than 100 alcoholic liver disease cases.…”
Section: Other Cyp Polymorphism-disease Associationsmentioning
confidence: 99%